Composition, diversity, and value of ecological importance in Andean grassland ecosystems according to the altitudinal gradient in the Huacracocha micro-watershed, Peru - Yaranga Cano, Raul Marino; Pizarro Carcausto, Samuel Edwin; Cano, Deyvis; Chanamé, Fernan C.; Orellana, Javier A. (Sciencedomain International, 2023)
Aims: determine the composition and floristic diversity, the similarity between sites based on the distribution of species in the altitudinal gradient, and determine the value of ecological importance, in Andean grassland ecosystems.